Adaption of Theoretical Adsorption Model on Coal: Physical Structure - Guodai, Wu; Linhua, Pan; Bingxiang, Huang; Jinhua, Luan; Ye, Zhang; Ruigang, Zhang; Zheng, Sun (Frontiers in Earth Science, 2021)
With the motivation to investigate the role of coal physical structure on the adsorption performance of coal reservoir, 18 different types of coal samples with different coal structure were collected from 6 coal profiles of four production mines located at China. The adsorption characteristics of CH4 on coal samples with different coal structure were examined, then experimental results were fitted and analyzed by Langmuir model and adsorption potential model (D-R, D-A). The prominent factors in terms of adsorption capacity of coal with different coal structure and its adaptability to the model were discussed. Results indicate: (a) under the condition of similar coal rank, the adsorption performance of coal is governed by coal-rock composition and adsorption heat, the effect of structural deformation on the adsorption performance of coal is not obvious; (b) Langmuir model has a certain adaptability to coal samples with different coal structure, while D-R model is evidently not suitable to describe coal samples with scaly coal, part of broken coal with small vitrinite content; (c) D-A model has a high adaptability to coal samples with various coal structure types, and the stronger the coal deformation is, the higher the accuracy is.